Change in Cardiovascular Risk Factors with Progression of Kidney Disease - Fried, Linda F. (S. Karger AG, 2009)
BACKGROUND: Prior studies evaluating the relationship of kidney disease with cardiovascular risk factors have been limited by their cross-sectional design. We evaluated the change in lipids, inflammatory and procoagulant biomarkers with decline in kidney function in a nested case-cohort study in the Cardiovascular Health Study, a community-based study of adults aged >65 years. METHODS: Individuals with an increase in serum creatinine ≥0.3 mg/dl (baseline to 3 years later, n = 207) were matched to controls of similar age, race, gender, diabetes and baseline serum creatinine, but whose change in creatinine was <0.3 mg/dl. Baseline and change in risk factors were analyzed with conditional logistic regression. RESULTS: Changes in C-reactive protein were similar. In contrast, cases had larger increases in fibrinogen (OR 1.38 per standard deviation, 95% confidence interval 1.08–1.76) and factor VIII [1.38 (1.10–1.72)] and larger decreases in HDL [OR 0.80 (0.64, 1.00)]. Change in interleukin-6 was greater in cases than controls, but this did not persist after multivariate adjustment. However, in linear regression, change in interleukin-6 was correlated with change in creatinine. CONCLUSION: Cardiovascular risk factors and kidney function may change concurrently. This could lead to an increased risk of cardiovascular disease as kidney function worsens.